Constructing chaotic transformations with closed functional forms. (4th September 2006) - Huang, Weihong
Abstract : The properties of complete chaotic unimodal transformations with closed functional forms are examined and the necessary and sufficient conditions are provided to construct such transformations. Theoretical findings are verified with computer simulations.